First-in-child phase I/II study of the dual mTORC1/2 inhibitor vistusertib (AZD2014) as monotherapy and in combination with topotecan-temozolomide in children with advanced malignancies: arms E and F of the AcSé-ESMART trial. (November 2021) - Morscher, Raphael J.; Brard, Caroline; Berlanga, Pablo; Marshall, Lynley V.; André, Nicolas; Rubino, Jonathan; Aerts, Isabelle; De Carli, Emilie; Corradini, Nadège; Nebchi, Souad; Paoletti, Xavier; Mortimer, Peter; et al.
Abstract: Aim: Arms E and F of the AcSé-ESMART phase I/II platform trial aimed to define the recommended dose and preliminary activity of the dual mTORC1/2 inhibitor vistusertib as monotherapy and with topotecan-temozolomide in a molecularly enriched population of paediatric patients with relapsed/refractory malignancies. In addition, we evaluated genetic phosphatidylinositol 3-kinase (PI3K)/AKT/ mammalian (or mechanistic) target of rapamycin (mTOR) pathway alterations across the Molecular Profiling for Paediatric and Young Adult Cancer Treatment Stratification (MAPPYACTS) trial (NCT02613962). Experimental design and results: Four patients were treated in arm E and 10 in arm F with a median age of 14.3 years. Main diagnoses were glioma and sarcoma. Dose escalation was performed as per the continuous reassessment method, expansion in an Ensign design. The vistusertib single agent administered at 75 mg/m 2 twice a day (BID) on 2 days/week and vistusertib 30 mg/m 2 BID on 3 days/week combined with temozolomide 100 mg/m 2 /day and topotecan 0.50 mg/m 2 /day on the first 5 days of each 4-week cycle were safe. Treatment was well tolerated with the main toxicity being haematological. Pharmacokinetics indicates equivalent exposure in children compared with adults. Neither tumour response nor prolonged stabilisation was observed, including in the 12 patients whose tumours exhibited PI3K/AKT/mTOR pathway alterations. Advanced profiling across relapsed/refractory paediatric cancers of the MAPPYACTS cohort shows genetic alterations associated with this pathway in 28.0% of patients, with 10.5% carrying mutations in the core pathway genes. Conclusions: Vistusertib was well tolerated in paediatric patients. Study arms were terminated because of the absence of tumour responses and insufficient target engagement of vistusertib observed in adult trials. Targeting the PI3K/AKT/mTOR pathway remains a therapeutic avenue to be explored in paediatric patients. Clinical trial identifier: NCT2813135 . Highlights: Dual mammalian (or mechanistic) target of rapamycin (mTOR) inhibition by vistusertib is well tolerated in the paediatric population. Vistusertib monotherapy and with TOTEM exhibits insufficient antitumour response. mTOR pathway–activating mutations do not sensitise to vistusertib therapy.